Preferences for Online and/or Face-to-Face Counseling among University Students in Malaysia - Wong, Kah P.; Bonn, Gregory; Tam, Cai L.; Wong, Chee P. (Frontiers in Psychology, 2018)
Increasingly, online counseling is considered to be a cost effective and highly accessible method of providing basic counseling and mental health services. To examine the potential of online delivery as a way of increasing overall usage of services, this study looked at students’ attitudes toward and likelihood of using both online and/or face-to-face counseling. A survey was conducted with 409 students from six universities in Malaysia participating. Approximately 35% of participants reported that they would be likely to utilize online counseling services but would be unlikely to participate in face-to-face counseling. Based on these results, it is suggested that offering online counseling, in addition to face-to-face services, could be an effective way for many university counseling centers to increase the utilization of their services and thus better serve their communities.